Discussion Panel Giving Human Factors/Ergonomics Away: How can we bring the benefits of HF/E to nursing?. (September 2013) - Klein, Martina I.; DeLucia, Patricia R.; Doig, Alexa; Drews, Frank; Durso, Francis T.; Miller, Anne
Patients spend the most time with nurses compared with other health care providers, and patient outcomes are directly related to the quality of nursing care. Unfortunately, nursing work systems are often not designed to accommodate the limits and capabilities of perceptual, cognitive, and physical processes, which can result in errors. The Institute of Medicine estimated that hospital patients experience one medication error each day. Increasingly, technology is relied upon to reduce errors and improve work efficiency. However, new technologies can lead to unintended consequences. Applying principles of human factors and ergonomics (HF/E) to improve nursing work systems and the technologies nurses use has the potential for significant improvements in the quality of patient care. Incorporating HF/E into the nursing domain presents challenges. Conducting research in the nursing environment poses unique logistical issues, and implementing HF/E recommendations requires that nursing personnel accept HF/E as beneficial. The purpose of this panel session is to discuss issues that HF/E professionals encounter when they attempt to incorporate HF/E into the nursing domain. The panelists will summarize the work that they have done with nurses and describe challenges and successes. The panel will invite the audience to discuss ways to address challenges, increase successes, and identify lessons learned in other domains that may benefit nursing.